AKTIVITAS ANTIBAKTERI MINYAK ESENSIAL LAVENDER DAN LEMON TERHADAP PATOGEN PENYEBAB INFEKSI SALURAN PERNAPASAN AKUT : STUDI IN VITRO - Nayla Aziza Dwigusfita; Aliyah Siti Sundari; Hanny Febrianti Salsabillah; Zahra Shopie Ananta; Hanna Zuhayla Rahmawaty; Dimas Rizky Permana (LPPM Universitas Abdurrab, 2025)
Acute Respiratory Infection (ARI) is a highly prevalent infectious disease in Indonesia, reaching 25% in 2013. Antibiotic therapy remains the primary treatment option; however, irrational use has led to bacterial resistance. Therefore, alternative treatments based on natural ingredients are needed. Lavender (Lavandula angustifolia) and lemon peel (Citrus limon) essential oils contain bioactive compounds such as linalool, linalyl acetate, DL- limonene, and γ-terpinene, which possess potential antibacterial properties. This study aimed to evaluate the antibacterial activity of a combination of lavender and lemon essential oils against ARI-causing bacteria. The research was conducted experimentally in the laboratory using the disc diffusion method on Mueller-Hinton Agar (MHA). Test samples included lavender oil, lemon oil, their combination, positive control (ciprofloxacin 5 µg), and negative control (aquadest). The antibacterial activity was tested against Staphylococcus aureus, Streptococcus pyogenes, Klebsiella pneumoniae, Escherichia coli, and Pseudomonas aeruginosa with four replications. Data were analyzed using one-way ANOVA with a 95% confidence level. Results showed inhibition zones ranging from 13–20.5 mm in E. coli, S. aureus, and K. pneumoniae; slight inhibition against S. pyogenes; and no activity against P. aeruginosa. The highest effectiveness was observed in F1 against E. coli and F3 against S. aureus. The combination of lavender and lemon essential oils shows potential to be developed as natural antibacterial agents supporting alternative therapy for ARI